Pain as Sign and Symptom: A Semiotic Analysis of Nursing Clinical Practice and Research - Long, Thomas (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2019)
Physical pain, far from being a monolithic sensation, is a complex and varied somatic response to trauma or pathophysiology. The body registers pain in response to a threat to bodily wholeness; the patient or clinician interprets pain, seeking to associate the pain with its cause (diagnosis or etiology) in order to undertake a remedy and to predict its future course (prognosis). In nursing clinical practice, where symptom assessment and management are central to the scope of practice, reading pain as sign (the clinician’s empirical observation) or as symptom (an experience reported by the patient) entails complex interpretation and translation of the body’s manifestations. This article will make explicit the semiotic dimensions of nursing pain research (and its concomitant implications for clinical practice) in two cases : Xiaomei Cong’s research into procedural pain in infants in neonatal intensive care units (NICU) and Deborah Dillon McDonald’s research into pain communication between older adults with osteoarthritis or post-surgical pain and their healthcare providers.